2013
DOI: 10.1271/bbb.120638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Fermented Brown Rice Extract on the Gastrointestinal Function in Methotrexate-Treated Rats

Abstract: We investigated the protective effect of a hydrous ethanol extract of brown rice fermented with Aspergillus oryzae (ERF) which contained nucleobases and low fiber on the methotrexate (MTX)-induced gastrointestinal damage in rats. The rats were assigned to three groups: control (CON), MTX, and MTX-ERF. The rats in the CON and MTX groups were fed for 4 weeks on a basal diet, and those in the MTX-ERF group were fed on a 9.16% ERF-containing basal diet. The rats in the MTX and MTX-ERF groups were administered with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These interactions are mediated by the neural, endocrine, and immune systems to maintain intestinal homeostasis [2]; however, homeostatic dysfunction can significantly affect host immunity and the course of chronic inflammation [3]. Some probiotics and polysaccharides have been found to regulate intestinal and immune homeostasis; for instance, probiotic Bifidobacterium bifidum alleviates dysbiosis and constipation in mice induced by a low-fiber diet [4], while grains fermented with Aspergillus oryzae can protect against chronic constipation and gastrointestinal damage [5,6]. In addition, the soluble dietary fiber β-1,3-glucan from seaweed has been shown to suppress intestinal inflammation in mouse models of human inflammatory bowel disease by increasing the Lactobacillus population and the number of regulatory T cells in the colon [7].…”
Section: Introductionmentioning
confidence: 99%
“…These interactions are mediated by the neural, endocrine, and immune systems to maintain intestinal homeostasis [2]; however, homeostatic dysfunction can significantly affect host immunity and the course of chronic inflammation [3]. Some probiotics and polysaccharides have been found to regulate intestinal and immune homeostasis; for instance, probiotic Bifidobacterium bifidum alleviates dysbiosis and constipation in mice induced by a low-fiber diet [4], while grains fermented with Aspergillus oryzae can protect against chronic constipation and gastrointestinal damage [5,6]. In addition, the soluble dietary fiber β-1,3-glucan from seaweed has been shown to suppress intestinal inflammation in mouse models of human inflammatory bowel disease by increasing the Lactobacillus population and the number of regulatory T cells in the colon [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the anti-colitis effects of processed RB in animal models, focusing on rice bran oil [ 12 ], brown rice fermented by Aspergillus oryzae [ 5 , 13 ], enzyme-treated rice fiber [ 8 ], and RB fermented by Saccharomyces cerevisiae and Lactobacillus plantarum [ 3 ]. Processed RB is enriched for different ingredients to varying degrees because of different fermentation processes and preparation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Ochiai et al [28] reported the preventive effects of a hydrous ethanol extract of FBRA on gastrointestinal damage in a methotrexate (MTX)-treated animal model. FBRA extract contains nucleobases and low dietary fiber content, although FBRA generally contains abundant dietary fiber.…”
Section: Anti-colitis Effects Of Brown Rice Fermented By Aspergillus mentioning
confidence: 99%
“…FBRA extract contains nucleobases and low dietary fiber content, although FBRA generally contains abundant dietary fiber. Moreover, MTX treatment of an animal model resulted in malabsorption syndrome through severe malabsorption of nutrients and diarrhea [28]. They reported that oral administration of FBRA extract attenuated diarrhea, increased protein content in the small intestine, and improved survival [28].…”
Section: Anti-colitis Effects Of Brown Rice Fermented By Aspergillus mentioning
confidence: 99%